The Performance of Floating House Sub Structure in Tempe Lake - Rusdianto Rusdi; Nasruddin Nasruddin; Hartawan Madeali (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
This study aims to reveal the lifting power of the bamboo raft in holding the weight of the house on stilts so that it stays floating on the water. This research was conducted on the shores of Lake Tempe, precisely in Laelo Village, Tempe District, Wajo Regency. The method used in this research is a field study to determine the real situation in the field so that the real condition of the floating house is known. Furthermore, calculating the load used on the floating house based on the results of field studies. The final stage of the research is to test the raft lifting capacity of the floating house. The data will be analyzed according to Archimedes' Law, so that it can be seen that the bamboo raft can stay afloat even though it is given an Architectural building as heavy as a simple stilt house. The results of this study revealed that the average number of bamboos used as a raft was 175 stalks, and the mean diameter of bamboos was 7.67 cm or 0.077 m. It is known that the volume of the rod segment cavity is 0.103 m³, so the total volume between sections on the floating raft on Lake Tempe is 18.058 m³. The lifting capacity of bamboo rafts is directly proportional to the volume of bamboo joints used as rafts. The experimental test results obtained revealed that the lifting capacity of bamboo per m3 was 874.51 kg, so the lifting capacity of the bamboo raft in Tempe Lake was 18.058 m³ x 874.51 kg / m³ = 15,789.13 kg. While the results of the calculation of the burden of a simple house are known by calculating the house's own load and the living load experienced by the house, and the weight of the house is 9,314.121 kg. With the ability to lift a bamboo raft of 15,789.13 kg, the difference between the lifting capacity of the bamboo raft and the weight of the floating house is 6,475.01 kg. The ideal number of bamboo culms is 129 with a safety factor of 25%. There is an efficient use of 46 bamboo sticks.